2004
DOI: 10.1001/archpsyc.61.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Latent Class Analysis to Empirically Define EatingDisorder Phenotypes

Abstract: The presence of obsessive-compulsive features differentiates among individuals with restricting AN. Similarly, the combination of low weight and multiple methods of purging distinguishes among individuals with binge eating and purging behaviors. These results support some of the distinctions drawn within the DSM-IV-TR among eating disorder subtypes, while introducing new features to define phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
156
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 46 publications
21
156
3
Order By: Relevance
“…Although research indicates that the overarching diagnosis of ''eating disorder'' is relatively stable, 3 several studies suggest that there is considerable longitudinal instability of the specific eating disorder diagnoses of AN, BN, and EDNOS in treatment samples, resulting from recovery, relapse, and crossover between and within the eating disorder diagnoses. 3,[4][5][6] The recovery rates for AN and BN were moderate to high at each of the follow-up assessments in Fichter and Quadflieg study, which is similar to the rates reported by Ben-Tovim et al, 7 who found that at 5-year follow-up, 56% of patients with AN, 74% of patients with BN, and 78% of patients with EDNOS no longer met criteria for any eating disorder diagnosis.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andsupporting
confidence: 74%
“…Although research indicates that the overarching diagnosis of ''eating disorder'' is relatively stable, 3 several studies suggest that there is considerable longitudinal instability of the specific eating disorder diagnoses of AN, BN, and EDNOS in treatment samples, resulting from recovery, relapse, and crossover between and within the eating disorder diagnoses. 3,[4][5][6] The recovery rates for AN and BN were moderate to high at each of the follow-up assessments in Fichter and Quadflieg study, which is similar to the rates reported by Ben-Tovim et al, 7 who found that at 5-year follow-up, 56% of patients with AN, 74% of patients with BN, and 78% of patients with EDNOS no longer met criteria for any eating disorder diagnosis.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andsupporting
confidence: 74%
“…The separation of our groups containing low weight patients into two non-binge eating or purging latent groups is consistent with some of the adult findings. [15][16] Two of the adult studies identified latent groups resembling AN that were distinguished by level of psychopathology, [15][16] with one of these being a group that endorsed low levels of both eating disorder cognitions as well as depression and anxiety, but at the same time reporting treatment-seeking and medical concerns at levels that were comparable to the other latent groups. 15 Yet, even if the groups identified in this youth sample resemble those empirically-derived in adults, they may not be the same.…”
Section: Discussionmentioning
confidence: 99%
“…12 LPA has the advantage of allowing for the inclusion of continuous indicators while LCA is limited to categorical indicators. To date, this empirical classification research has been limited to adult samples, [13][14][15][16][17][18][19][20] with the exception of one recent report combining adolescents and young adults. 21 In adult samples, this research has demonstrated that LCA/LPA reliably identify clinically meaningful subgroups of individuals with eating disorders including those that resemble AN, BN, and one particular type of EDNOS characterized by binge eating without purging (binge eating disorder [BED]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations